ETHNOGRAFISCHE ONLINE-ARCHIVE ALS PARÖMIOLOGISCHES WERKZEUG : NUTZUNGSSZENARIEN DES WOSSIDLO DIGITAL ARCHIVE (WOSSIDIA) - Schmitt, Christoph (Proverbium - Yearbook, 2019)
The article aims to demonstrate the connectivity of an online folklore archive to proverbial research and proverb databases. The case study is WossiDiA, which presents the exensive (Low German language based) regional ethnographic collection of Mecklenburgʼs field-worker Richard Wossidlo (1859-1939). The challenge of the WossiD-iA-project was to model the idiosyncratic nature of this tradition ar-chive. About two million resarch notes, mostly small-scale information, are highly networked by hypergraphs. Some examples show how to extract proverbs from the digital archive. Variant relationships, social data of the informants, and other aspects of knowledge production, can also be included. Experiences within the transatlantic Big Data-project ISEBEL (Intelligent Search Engine for Belief Legends), in which WossiDiA actually participates, provide some ideas on how WossiDiA can be connected to proverbial databases.